Synopsis of Phengodes Illiger, 1807 (Coleoptera: Phengodidae) of Mexico with the description of seven new species - Uchima-Taborda, Diego; Vega-Badillo, Viridiana; Zaragoza-Caballero, Santiago (Zootaxa, 2026)
Phengodes Illiger, 1807 is one of the most diverse genera of Phengodidae (Coleoptera) in Mexico. However, there is an information gap that challenge to conduct studies on this group. In light of this problem, a synopsis of the genus in Mexico is needed. The present research documents with the diagnoses and photographic material, the 14 previously reported species for the country and describes seven more: Phengodes dugesi sp. nov., Phengodes mime sp. nov., Phengodes dichoclypeus sp. nov., Phengodes huatulcoensis sp. nov., Phengodes mejiabernale sp. nov., Phengodes wittmeri sp. nov., and Phengodes yaxoquintelaensis sp. nov., bringing the total of Phengodes species in Mexico to 21. Occurrence maps and a taxonomic key are provided to identify the species of the country. This work contributes to the understanding of the diversity and distribution of Phengodes in Mexico, at increasing the knowledge about the diversity and morphology of the group.